Effects of Aerobic Exercise on Sleep Quality and Mental Health of College Students - Lu Li (Hindawi-Wiley, 2022)
Objective. In recent years, people's living standards have been greatly improved, but at the same time, it also brings many health problems, among which mental health problems and sleep problems of college students are important problems. The aim of the study is to explore the effect of physical activity intervention on college students' mental health and provide a new way of thinking for colleges and universities to carry out mental health interventions. Methods. This paper focuses on the physical health problems of college students and explores the relationship between aerobic exercise, emotion, and sleep quality among college students. The SPSS statistical method was used to analyze the differences in aerobic exercise, emotion, and sleep quality among college students in terms of demographic variables; to explore the relationship between aerobic exercise, emotion, and sleep quality; and to construct a structural equation model using the relationship between them. Results/Discussion. This study explores the relationship between aerobic exercise and sleep quality and psychological health of college students, further analyzes the path model of the role of aerobic exercise and psychological health on sleep quality of college students, and verifies it through experiments, which proves to help universities and relevant departments understand the current situation of exercise and sleep quality of college students and provide timely and effective design of mandatory aerobic exercise courses for college students who lack exercise and have sleep problems. At the same time, it helps college students to understand their sleep situation and adjust their aerobic exercise courses according to their sleep status.